2014
DOI: 10.1002/jcp.24614
|View full text |Cite|
|
Sign up to set email alerts
|

Nanotopography Directs Mesenchymal Stem Cells to Osteoblast Lineage Through Regulation of microRNA-SMAD-BMP-2 Circuit

Abstract: The aim of this study was to investigate if chemically produced nanotopography on titanium (Ti) surface induces osteoblast differentiation of cultured human bone marrow mesenchymal stem cells (hMSCs) by regulating the expression of microRNAs (miRs). It was demonstrated that Ti with nanotopography induces osteoblast differentiation of hMSCs as evidenced by upregulation of osteoblast specific markers compared with untreated (control) Ti at day 4. At this time-point, miR-sequencing analysis revealed that 20 miRs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
56
0
20

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 67 publications
(81 citation statements)
references
References 36 publications
4
56
0
20
Order By: Relevance
“…The SEM and AFM analyses confirmed that a nanotopography characterized by nanopits is generated by etching the Ti surface with H 2 SO 4 /H 2 O 2 solution, similar to our previous findings . Also, in agreement with observations that collagen coating does not alter the Ti topography, no differences in the nanotopographic features of the Ti surface were detected after the collagen layer deposition .…”
Section: Discussionsupporting
confidence: 91%
“…The SEM and AFM analyses confirmed that a nanotopography characterized by nanopits is generated by etching the Ti surface with H 2 SO 4 /H 2 O 2 solution, similar to our previous findings . Also, in agreement with observations that collagen coating does not alter the Ti topography, no differences in the nanotopographic features of the Ti surface were detected after the collagen layer deposition .…”
Section: Discussionsupporting
confidence: 91%
“…The absence of both osteo-and adipogenic differentiation is a first major finding since uncontrolled and unsuitable differentiation processes must be avoided in a putative therapeutic setting especially in ectopic settings like the neural system. It has been demonstrated previously that micro-or nanostructuring of the substrate can induce neuronal or osteogenic differentiation processes of MSCs [34][35][36][37][38][39]. As one example, investigations with square-shaped or round-shaped microwells in polystyrene (side length or diameter of 10, 25, and 50 µm, respectively) showed that only the substrate with 50 µm square-shaped microwells promoted osteogenic differentiation of adipose tissue-derived MSCs [40].…”
Section: Discussionmentioning
confidence: 95%
“…Much work has been carried out to unravel the mechanisms involved in surface contact and gene expression. The principal contact point is the subcellular macromolecular focal adhesion, which is joined between the cell cytoskeleton and extracellular matrices [7]. The association and clustering of these objects with the matrix is an important effect that allows sensing of mechanical forces.…”
Section: Surfaces For Cell Proliferation and Differentiationmentioning
confidence: 99%
“…Programmable biomaterials with influential topography are a realistic prospect for interplay with human cells and bacteria cells. There is tremendous array of data showing the diverse pairings of nanotopography arrays with fibroblasts, endothelial, epithelial, pluripotent, mesenchymal and embryonic [3][4][5][6][7][8][9][10][11][12]. There are numerous instances of conflicting results but there are strong trends emerging.…”
Section: Introductionmentioning
confidence: 99%